Financial Performance Analysis of Banks Listed on the Indonesia Stock Exchange for the 2022–2025 Period - Nursidin, M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The purpose of this study is to determine the financial performance of banks listed on the Indonesia Stock Exchange during the 2022–2025 period based on the calculation of Gross Profit Margin, Quick Ratio, and Debt to Asset Ratio. The data used are secondary data collected through documentation study techniques. The data analyzed in this research consist of banks listed on the Indonesia Stock Exchange from 2022 to 2025. Based on the results of data analysis, it can be concluded that the bank soundness analysis, as seen from the Gross Profit Margin, shows that PT Bank Rakyat Indonesia Tbk., PT Bank Negara Indonesia Tbk., and PT Bank Tabungan Negara Tbk. are in a very healthy condition. This indicates that these three banks have the ability to generate profit from their main operations after accounting for direct costs. The Quick Ratio of PT Bank Rakyat Indonesia Tbk. is categorized as fairly healthy, indicating that the bank has adequate liquidity to meet its short-term obligations. The Quick Ratio of PT Bank Negara Indonesia Tbk. is also categorized as fairly healthy, showing sufficient liquidity to fulfill its short-term liabilities. Meanwhile, the Quick Ratio of PT Bank Tabungan Negara Tbk. is categorized as unhealthy, indicating that the bank experiences difficulties in meeting its short-term obligations, as it is unable to cover its liabilities using its available liquid assets. The Debt to Asset Ratio of PT Bank Rakyat Indonesia Tbk., PT Bank Negara Indonesia Tbk., and PT Bank Tabungan Negara Tbk. is categorized as very healthy. This indicates that the three banks have stable financial conditions and are better able to bear risk. With a low debt-to-asset ratio, banks can maintain strong financial resilience in facing market fluctuations or financial crises.